Recurrence of subsquamous dysplasia and carcinoma after successful endoscopic and radiofrequency ablation therapy for dysplastic Barrett’s esophagus - Lee, J. K.; Cameron, R. G.; Binmoeller, K. F.; Shah, J. N.; Shergill, A.; Garcia-Kennedy, R.; Bhat, Y. M. (Endoscopy, 2013)
Barrett’s esophagus with dysplasia is commonly treated with radiofrequency ablation (RFA). Despite its effectiveness, a concern of any ablative technique is the development of subsquamous intestinal metaplasia, which could have potential for future neoplastic progression. To date, 34 cases of subsquamous neoplasia have been described in the literature after various ablation therapies. However, only three cases of subsquamous neoplasia have been reported after successful RFA treatment of dysplastic Barrett’s esophagus. In this case series, we report on four additional cases of subsquamous neoplasia detected after successful endoscopic resection and RFA for neoplastic and dysplastic Barrett’s esophagus. All four patients were treated successfully with endoscopic resection of their recurrent subsquamous neoplastic and dysplastic lesions. This case series highlights the need for continued surveillance following successful treatment of dysplastic Barrett’s esophagus with RFA.